2016 IEEE 30th International Conference on Advanced Information Networking and Applications (AINA) 2016
DOI: 10.1109/aina.2016.95
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Workflows for Microservices: Genericity in Jolie

Abstract: Microservices is an architectural style inspired by service-oriented computing that has recently started gaining popularity. Jolie is a programming language based on the microservices paradigm: the main building block of Jolie systems are services, in contrast to, e.g., functions or objects. The primitives offered by the Jolie language elicit many of the recurring patterns found in microservices, like load balancers and structured processes. However, Jolie still lacks some useful constructs for dealing with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 6 publications
0
27
0
Order By: Relevance
“…Code snippets of standard specification languages such as Javascript, JSON, Node.js and Ruby were used to describe the data model of messages communicated between microservices. A novel programming language called Jolie [35] was used to program and describe the architecture of its IDE which is also built using microervices. Based on the previous analysis, it can be noted that modeling microservices with UML standard notations is comparable to creating another comprehensive modeling notation and also comparable to the use of informal drawings with free boxes and lines accompanied by a narrative.…”
Section: Discussionmentioning
confidence: 99%
“…Code snippets of standard specification languages such as Javascript, JSON, Node.js and Ruby were used to describe the data model of messages communicated between microservices. A novel programming language called Jolie [35] was used to program and describe the architecture of its IDE which is also built using microervices. Based on the previous analysis, it can be noted that modeling microservices with UML standard notations is comparable to creating another comprehensive modeling notation and also comparable to the use of informal drawings with free boxes and lines accompanied by a narrative.…”
Section: Discussionmentioning
confidence: 99%
“…It has has been shown that scalability issues can naturally be solved by use of microservice architecture [11,12], and that large-size companies have already implemented migrations to this architectural style [13]. Furthermore, specific programming languages are available to support microservice architecture [14,15]. Full deployment of the system should consider a migration to microservice, possibly making use of a suitable language and relying on the expertise of our team on the matter.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work on the type system has been done, however focusing mostly on dynamic type checking. Safina extended the dynamic type system as described in [28], where type choices have been added in order to move computation from a process-driven to a data-driven approach.…”
Section: Related Workmentioning
confidence: 99%
“…The project implementation considers using a stack during the recursive checking of the nodes as illustrated in section 4.4. The decision of using an SMT-solver, instead of more lightweight techniques, was made in order to allow a future straightforward integration of Refinement Types into the type checker, objective on which our team is already working [28,31]. Furthermore, relying on a solid existing technology allowed us to prototype and release a proof of concept of the type checker in a shorter period of time.…”
Section: Static Type-checking Implementationmentioning
confidence: 99%